An investigation of the effect of low salary on teachers’ academic performance in Liberia - Sucuoğlu, Esen (2023)
It is a widely known fact that salaries are one of the biggest factors affecting employees working performance regardless of the professional identity in any part of the world. As the title suggests this study was carried out on the issue of the administrative impact of low salary on teachers' performance in Liberia. The major goal was to uncover issues that both instructors and kids encounter as a result of low salaries. The study used a quantitative approach, with a total population of 1500 people and a sample size of 150 people, using a simple random sampling method. More than half of the instructors had evident effects of functioning fairly in the classroom and inconsistent attendance, according to the data. The data revealed that more than half of the instructors were paid low wages with little or no additional perks or allowances. To attain their targeted outcomes, both the national government and school authorities will need to do more. According to the findings, increases in teacher attributes are most likely to lead to significant gains in student performance. As a result, excellent education can only be ensured by great instructors. Gender, age, race, wage, personality, behavior, attitude, education, training, experience, job satisfaction, motivation, morale, ability, and skill are all listed as elements that influence a teacher's performance. Wages remain an important determinant, according to this study, which extensively analyzed and evaluated these effects.